Digital textile patterns inspired by themes from the late 1950s/early 1960s - Pickett, Meagan Lynette (Kansas State University, 2010)
Inspired by people and objects of the late 1950s/early 1960s, textile patterns were created to use as a tool in the education of children through play. Four themes were developed, with three main prints in each theme. These twelve prints had a coordinating print and solid colors designed, and were utilized in the development of paper doll clothing. Representing the look of Jacqueline Kennedy, the paper dolls feature a pearl necklace, sunglasses, and a brunette hairstyle. Fabric was also printed on using a home-based ink jet printer, and used to construct a garment for an 18-inch, three dimensional doll. The final outcomes were exhibited in a display window, with an interactive element for adults and children at the opening reception.
Keywords: Textile patterns; Ink jet printing; Themes from the late 1950s/early 1960s; Children's educational play; Textile Technology (0994)